The effect of systemic chemotherapy on hematological profiles in lung cancer patients - Amarudin, Amarudin; Munir, Sri Melati (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Cancer is a disease characterized by uncontrolled cell growth in one or both lungs originating from epithelial cells. In Indonesia, lung cancer ranks fourth among all cancer types and is the second leading cause of death after cardiovascular diseases. Management of lung cancer involves various therapeutic modalities, including surgery, radiotherapy, chemotherapy, and combination therapy. Certain chemotherapeutic agents, such as cisplatin and carboplatin, are known to have a narrow therapeutic index and high toxicity, so inappropriate regimen selection or dosing may result in serious adverse effects or even death. All chemotherapy agents carry the potential for toxicity, including both hematological and non-hematological effects, with hematological toxicities commonly manifesting as anemia, leukopenia, and thrombocytopenia of varying severity. Objective: This study aimed to determine the hematologic profile in patients after chemotherapy. Methods: This study was a descriptive research with a cross-sectional design using a total sampling technique. During the August-December 2023 period, 36 lung cancer patients met the inclusion criteria at Arifin Achmad Hospital, namely lung cancer patients with adenocarcinoma or squamous cell carcinoma who underwent advanced chemotherapy with a cycle of 21 days in the August-December 2023 period. Results: Of the 36 patients, 29 (80.56%) were male. The highest age of patients undergoing chemotherapy was ≥ 40 years (94.44%). Changes in the hematological profile after chemotherapy occurred in 14 patients (38.89%), with the most common hematological profile being anemia. Conclusion: The use of chemotherapy regimens can cause changes in the hematologic profile, including anemia, leukopenia, and thrombocytopenia.